Karakterisasi Sifat Fisikokimia Pektin Kulit Jeruk Keprok Batu 55 (Citrus reticulata B), Jeruk Siam (Citrus nobilis var. microcarpa), Jeruk Manis Pacitan (Citrus sinensis L, Jeruk Nipis (Citrus aurantifolia swigle), dan Jeruk Lemon (Citrus limon L) yang Tumbuh di Kota Batu - Anis Febrianti Rahmanda K.W; Sukardi Sukardi; Warkoyo Warkoyo (Food Technology and Halal Science Journal, 2021)
Abstract. Utilization of orange peel waste in Batu City needs to be done to increase the selling power of consumers by extracting it as pectin. Pectin can be obtained using an extraction process. The stage of pectin extraction can affect the quality and quantity of the product. The extraction process will separate the pectin from the fruit tissue. This research was conducted with the production of orange peel flour as a material preparation process. The oranges used in this study were Batu 55 mandarin oranges (Citrus reticulata B), siam oranges (Citrus nobilis var. microcarpa), pacitan sweet oranges (Citrus sinensis L), lime (Citrus aurantifolia swigle), and lemons (Citrus limon L) which grows in the city of Batu. The next step was extraction using hydrochloric acid which was carried out using a nonfactorial randomized block design. The parameters observed were pectin yield, equivalent weight, methoxyl content, galacturonic acid content, esterification degree, moisture content, ash content, viscosity, colour intensity, and gel strength. The results showed that citrus peel varieties significantly affected yield, equivalent weight, galacturonic acid levels, degree of esterification, viscosity, and gel strength. Pectin with the best treatment based on the International Pectin Producers Association (IPPA) approach was shown in the Pacitan sweet orange peel variety with a galacturonic acid level of 99.15%, a viscosity of 88.06 cP, gel strength of 2.289 N, and an equivalent weight of 90.11 and resulted in yields. the most with a value of 24.20%. The pectin produced in this study is classified as high methoxyl pectin. Keywords: orange peel varieties, pectin, physicochemical properties   Abstrak. Pemanfaatan limbah kulit jeruk di Kota Batu perlu dilakukan untuk meningkatkan daya jual konsumen dengan mengekstraknya sebagai pektin. Pektin dapat diperoleh dengan cara proses ekstraksi. Tahapan ekstraksi pektin dapat mempengaruhi kualitas dan kuantitas produk. Proses ekstraksi akan memisahkan pektin dari jaringan buah. Penelitian ini dilakukan dengan pembuatan tepung kulit jeruk sebagai proses preparasi bahan. Jeruk yang digunakan pada penelitian ini adalah  jeruk keprok batu 55 (Citrus reticulata B), jeruk siam (Citrus nobilis var. microcarpa), jeruk manis pacitan (Citrus sinensis L), jeruk nipis (Citrus aurantifolia swigle), dan jeruk lemon (Citrus limon L) yang tumbuh di kota Batu.  Tahap selanjutnya adalah ekstraksi dengan menggunakan asam klorida yang dilakukan  menggunakan rancangan acak kelompok non faktorial. Parameter yang diamati adalah rendemen pektin, berat ekivalen, kadar metoksil, kadar asam galakturonat, derajat esterifikasi, kadar air, kadar abu, intensitas warna, viskositas dan kekuatan gel. Hasil  penelitian menunjukkan bahwa  varietas kulit jeruk berpengaruh nyata terhadap  rendemen, berat ekivalen, kadar asam galakturonat, derajat esterifikasi, viskositas dan kekuatan gel. Pektin dengan perlakuan terbaik berdasarkan pendekatan International Pectin Producers Association (IPPA)  ditunjukkan pada varietas kulit jeruk manis pacitan dengan nilai kadar asam galakturonat 99,15%, viskositas 88,06 cP, kekuatan gel 2,289 N, dan berat ekivalen 90,11 serta menghasilkan rendemen terbanyak dengan nilai 24,20%. Pektin yang dihasilkan dalam penelitian ini tergolong dalam high methoxyl pectin. Kata kunci : high methoxyl pectin, pektin, sifat fisikokimia,varietas kulit jeruk